Analysis of Reaction Time, Split Time and Final Time Records of Swimming Athletes in the Olympic Games on 2008-2021 - Bayu Agung Pramono; Yetty Septiani Mustar; Sri Sumartiningsih; Imam Marsudi; Agus Hariyanto; Muhammad Asrul Sidik; I Dewa Made Aryananda Wijaya Kusuma (OVS LLC, 2023)
Study purpose. This research aims to evaluate and analyze the Final Time (FT), Split Time (ST), and Reaction Time (RT) records of 100-meter butterfly swimmers in four Olympic events in order to provide benchmarks and standards for the development of swimming training. Materials and methods. This research combines quantitative and qualitative approaches. This study utilized a sample of 32 athletes ranked first through eighth who competed in the 100-meter butterfly at four Olympics: the 2008 Beijing Olympics, 2012 London Olympics, 2016 Rio Olympics, and 2021 Tokyo Olympics. It utilizes secondary data in which all time results are obtained from the website (http://www.fina.org). The descriptive statistics of mean and standard deviation were utilized for statistical analysis in this study. The Kolmogorov-Smirnov test was used to determine data normality. For comparing data between Olympiads, a one-way multi-comparison ANOVA was used to verify interactions between RT, ST, and FT across Olympiads. To determine the effect of RT and ST on FT, one-way linear regression was used with a significance level of p<0.05 as a standard. SPSS Inc., Chicago, IL, USA, was utilized for all analyses. Results. ST and RT were found to influence the achievement of FT in the 100-meter butterfly stroke, and RT had an effect of 0,712 (51%), for both male and female swimmers, on the achievement of the time in the first 50 meters. Conclusions. The conclusion is that both athletes and coaches are required to optimize the achievement of RT and ST in short-distance swimming because these two indicators play a crucial role in achieving the travel time of short-distance swimmers.